WILLEM DREES ON THE HUMANITIES: with Peter Harrison, "Defining and Defending the Humanities"; Michael Ruse, "Willem Drees on the Humanities"; Douglas F. Ottati, "Theology among the Human Humanities"; Lisa L. Stenmark, "Who are the Humanities For? Decolonizing the Humanities"; Donald L. Drakeman, "Some Second Thoughts about the Humanities"; and Willem B. Drees, "The Coherence and Character of the Humanities: A Reply to Critics.". Issue 3 (21st July 2021) - Ruse, Michael
Abstract: Do universities still need departments in the humanities—philosophy, history, languages, and so forth? Many today, particularly legislators with control over the funding of public universities, feel that the emphasis should be on, and only on, departments in the STEM field. Willem B. Drees, a former dean of humanities, makes a spirited defense of the worth of the humanities and of their continued place in higher education. This essay looks at Drees's arguments in a critical, yet appreciative, fashion. It is a debate we need to have.